Matczyne debiuty. Obrazy doświadczania pierwszych tygodni macierzyństwa - Mitręga, Anna (Kultura-Społeczeństwo-Edukacja, 2014)
Post-modernity has radically deformed the traditional ideas connected with entering the role of mother. Old ways of maternal initiation, passed from generation to generation, turned out to be inadequate. The aim of the research was to define socio-cultural factors that change defining and interpreting the key aspects of woman functioning in the first weeks after giving birth to a child. Basing on the gathered narrative interviews there were selected repetitive and subjectively meaning experiences creating the first period motherhood images. The free choice right experience and its psychological consequences, dilemma between natural and medical phenomena interpretation/ pregnancy, delivery, confinement and lactation/, emotional stress determinants or young mothers’ social perception were experience-creating elements of young women experiences. Pedagogical perspective in the analysis and interpretation of aspects connected with entering the role of mother may constitute a contribution in the approach to that present-day women’s life period, as well as in forming a social support for the motherhood.